PENGARUH KUALITAS PELAYANAN, DAYA TARIK DESTINASI DAN CITRA DESTINASI TERHADAP KEPUASAN PENGUNJUNG DI KAWUNG TILU, CIKARANG TIMUR, KABUPATEN BEKASI - Hairani Tarigan (Panorama Nusantara, 2020)
This research aims to know the influence of service quality, tourist attraction and destination image against visiting decision to Kawung Tilu, Bekasi. The data were collected through the questionnaires then measured by Likert scale score with a total of 100 the respondent visitors of Kawung Tilu Bekasi. Research using the method of double liner regression to analyze data. The results show a simultaneous service quality, tourist attraction and destination image against visiting destination. Service quality of the influential negative and not significant toward the visiting decision. While tourist attractions work a positive but has not significant effect against visiting decision. However destination image has positive and significant effect against visiting decision. This result means destination image influenced positively against visiting decision and the value is significantly to the visiting decision. The owner should pay more attention to the service quality and tourist attraction in order to improve visiting decision.